Lentiviral expression of GAD67 and CCK promoter‐driven opsins to target interneurons in vitro and in vivo. (January 2016) - Mantoan Ritter, Laura; Macdonald, Douglas C.; Ritter, Georg; Escors, David; Chiara, Francesca; Cariboni, Anna; Schorge, Stephanie; Kullmann, Dimitri M.; Collins, Mary
Abstract: Background: The ability to manipulate the activity of interneurons with optogenetic tools offers the possibility of interfering with diseases caused by altered neuronal inhibition and synchrony, including epilepsy and schizophrenia. To develop vectors for therapeutic approaches, targeting optogenetic constructs to interneurons is therefore a key requirement. We investigated whether the interneuron‐specific promoters glutamic acid decarboxylase (GAD)67 and cholecystokinin (CCK) allowed targeted lentiviral delivery of opsins to interneurons as a whole, or specifically CCK+ interneurons. Methods: We generated lentiviral (LV) plasmids encoding channelrhodopsin (ChR2) and halorhodopsin (NpHR) tagged with fluorophores and driven by GAD67 or CCK promoters. Adeno‐associated virus (AAV) and LV vectors carrying opsins driven by pyramidal cell promoters were used as controls. We transduced neuronal cultures and rodent brain in vivo, immunostained specimens 6–8 weeks after in vivo injection and 7–14 days after in vitro transduction, and evaluated volume and specificity of expression by confocal microscopy. Results: In vitro, 90% (19/21) of LV‐CCK‐NpHR2.0‐EYFP expressing neurons were CCK+. In vivo, LV‐GAD67‐ChR2‐mCherry was expressed in 2.6% (5/193), LV‐GAD67‐NpHR2.0‐EYFP in approximately 15% (43/279) and LV‐CCK‐NpHR2.0‐EYFP in 47% (9/19) of hippocampal GABA+ interneurons. GAD67 vectors expressed in larger volumes than CCK‐driven constructs. AAV vector controls achieved the largest expression volumes. Conclusions: LV‐CCK‐NpHR2.0‐EYFP may be useful for targeting CCK+ interneurons in culture. GAD67/CCK‐driven lentiviral constructs are expressed in vivo, although expression is not specific for interneurons. Overall, expression levels are low compared to opsins driven by pyramidal cell promoters. A better understanding of GAD67 and CCK promoter structure or alternative techniques is required to reliably target opsins to interneurons using viral vectors. Copyright © 2016 John Wiley & Sons, Ltd.